PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF ONLINE MENGGUNAKAN SCHOOLOGY BERBANTUAN WEB DESMOS MATERI GRAFIK FUNGSI KUADRAT - Nisyak, Robiatun; Trapsilasiwi, Dinawati; Fatahillah, Arif; Susanto, S; Murtikusuma, Randi Pratama (Department of Mathematics Education , University of Jember, 2018)
Abstract. This research aims to develop an online interactive learning media use assisted Schoology Desmos web for quadratic function graph. This is the kind of research the research development. The process of developing this learning media by using a customized Thiagarajan model or 4-D model. This development model consists of four stages, namely define, design, develop and disseminate. Trial subject of this research is students of class XI IPA 3 at SMAN Jenggawah with a total of 33 students. The results of the learning media validation in the valid criteria with a correlation coefficient of 0.94 including the